Suicide ideation, planning and attempt of heroin dependent patients - Koyuncu, Ayşe; Mırsal, Hasan; Yavuz, M. Fatih; Kalyoncu, Ö. Ayhan; Beyazyürek, Mansur (Journal of Dependence, 2003)
Objective: Substance dependence is the second leading cause of suicide in psychiatric disorders. In this study, suicidal features of heroin dependent patients were evaluated.Methods: A cross-sectional assessment of 100 inpatient heroin dependent patients without comorbid psychiatric disorder after 5-7 days of detoxification and 100 age, sex and education matched healthy controls was done. Sociodemographic information, clinical features related to substance use, suicide ideation, planning and attempt, the histories of sexual and physical abuse in childhood were collected by an informative questionnaire formed by the researchers. Diagnostic interviews according to DSM-IV criteria and Beck Depression and Beck Hopelessness Scales had been applicated to all participants.Results: The patient group had significantly higher rate of suicide ideation (X2 =43,78, df=1, p < 0.001), planning (X²=76.40, df=1, p < 0.001) and higher frequency of suicide attempts (X²= 22.58, df=1, p < 0.001) than control group did. Beck Depression Inventory and Beck Hopelessness Scale mean scores of the patient group were significantly higher than control group’s means.Conclusion: As the participants had no comorbid axis I disorder, the presence of heroin dependence was accepted to be the main reason of suicidal features of the study group. These results indicate the neccessity of a careful assessment of suicidal signs of heroin dependent patients not having axis I comorbidity .
Keywords: Heroin dependence; suicide ideation; suicide planning; suicide attempts